The Search for a model of public administration reform in Hong Kong: Weberian bureaucracy, new public management or something else? - Wong, Wilson (2013)
This article examines the limits of Western public administration models and the importance of a contextually embedded and empirically based approach of knowledge building in Asian public administration. It is attainted through a case study of the post-1997 public administration reform in Hong Kong to illustrate the mismatching between major models of Western public administration and the Asian domestic contexts. There are questions and doubts about both the goals and results of the public management reforms in Hong Kong. This article argues that post-handover reforms in Hong Kong cannot be fully explained by the normative and efficiency-oriented model of new public management self-claimed by the government. They are driven more by the political elite that emerged in the new political order after Hong Kong's transfer of sovereignty in 1997. Using administrative solutions to resolve political problems and address concerns on the domestic agenda has been a character of Hong Kong's administration, which is generalizable to other Asian countries. The article also sheds light on the bigger underlying questions raised in comparative public administration about the inadequate explanatory power of generalized Western public administration models and how the national context of Asian countries is more diverse and complicated from a so-called global model. - Reproduced.
Keywords: Public administration; Bureaucracy; Administrative reform - Hong Kong; Administrative reform